Perfil de maturidade do processo de desenvolvimento de produtos em empresas de pequeno e médio porte do setor de máquinas e implementos agrícolas - Simões, Julianita Maria Scaranello (2007)
The Brazilian agricultural machines and implements section has presented significant growth in recent years. This growth is related not only to Brazil s high performance in agrobusiness, but also to a technological progress seen in the sector of agricultural machines and implements that has enabled these companies greater insertion in the internal and external market. In view of such scenario, the product development process (PDP), if well structured and managed, becomes a business process that directly influences in the companies competitiveness increase. However, it is seen that with regard to the PDP in Brazilian small and medium-sized companies (SMCs) of agricultural machinery and implements (AMIs), very little is known about them as most of the publications on product development focus on the reality of large and multinational companies, which have a structure quite different from SMCs. In the few publications about the PDP in the SMCs of this sector, there are indications of a low degree of PDP structuring and management in these companies. Thus, the purpose of this dissertation is to characterize and analyze the profiles of management maturity of the product development process in small and medium sized Brazilian companies, of the agricultural machines and implements section, located in the state of São Paulo, so that the addressed actions of PDP improvements in these companies can be undertaken. A survey research in 40 companies (25 small-sized and 15 medium-sized) was conducted. An in loco interview was applied to the respective individual in-charge of PDP by means of a structured questionnaire. For the data analysis, descriptive statistics and multivariate analysis of clusters techniques was used. The sample indicated that all the SMCs of AMIs of the state of Sao Paulo presents a heterogeneous structure with respect to PDP management. Three groups of companies were identified in the sample with different maturity profiles of PDP: Group I (20% of companies in the sample), Group II (50% of the sample) and Group III (30% of the sample). The differences in the management of PDP were observed, especially among companies of Group I (smallest level of PDP maturity) and Group III (highest level of PDP maturity). However, despite differences in PDP management presented in the groups of companies, according to the literature on PDP management, all of the groups are in a basic (initial) maturity level of PDP. The sampled companies are in a basic maturity level, since most of them are in the stage of standardization of the development incremental cycle, and predominantly use only the CAD as a support tool for the PDP, and performance indicators are not yet used in the managing process. The identification of the maturity level, in which these companies are, helps in both the determination of activities that link the internal actions to improve the PDP of these companies, as in the proposal of specific public policies that encourage the improvement of product development for domestic companies of the sector.